The use of chemical pretreatment and meat tenderizer in reducing the cooking time of red kidney beans (Phaseolus vulgaris) - Tabayoyong, Luz B.
Different methods of chemical pretreatments and the use of papain in the form of a commercial tenderizer were compared in their efficacies in reducing the cooking time of red kidney beans. The chemicals used were 2.5% NaCl, 0.75% NaHCO3, and 0.25% Na2CO3. The levels of commercial tenderizer used were: 5%, 10%, 15%, and 20% solutions. Objective and subjective evaluations revealed that among the different treatments used the most efficient in reducing the cooking time of red kidney beans was soaking the beans for 20 hours in 0.75% NaHCO3. The second most effective method that can reduce the cooking time of red kidney beans was presoaking overnight in water followed by soaking in a 20% meat tenderizer for 30 minutes at 60°-80°C. The cooking time of the beans using 0.75% NaHCO3 was found to be about 20 minutes which is 60% less than the cooking time for beans which are simply soaked overnight in water. Beans soaked in water overnight followed by soaking in 20% tenderizer solution for 30 minutes at 60°-80°C can reduce the cooking of red kidney beans to about 25 minutes which is 50% less than the cooking time for beans soaked overnight in water. Beans soaked in 0.75% NaHCO3 was also found to be the most acceptable. Soaking in meat tenderizer seems to produce a slight bitterness in the taste.